Assessment of operability by means of CTPA and perfusion SPECT in patients with chronic thromboembolic pulmonary hypertension. (January 2016) - Grgic, Aleksandar; Miodek, Florian; Schäfers, Hans-Joachim; Held, Matthias; Kaiser, Ralf; Khreish, Fadi; Buecker, Arno; Bals, Robert; Kirsch, Carl-Martin; Wilkens, Heinrike
Background: Chronic thromboembolic pulmonary hypertension (CTEPH) can potentially be cured by pulmonary thrombendarterectomy (PEA), the criteria for differentiation between operable and non-operable patients are not standardized. Purpose: To retrospectively evaluate the value of rigidly registered computed tomography pulmonary angiography (CTPA) and single photon emission CT (SPECT) in differentiating for PEA. Material and Methods: Forty-nine patients with CTEPH (21 men; age, 58 ± 13 years) were evaluated by an interdisciplinary expert board using all available diagnostic information and their consensus statement as gold standard. For SPECT a lobe based perfusion score was visually assessed using the score of 0 (lack of perfusion) to 1 (normal perfusion) calculating percentage of vascular obstruction (PVO). By CTPA, vascular obstruction index (OI) of central, peripheral, and global PA-bed were determined. The accuracy of the alignment between CTPA and SPECT was determined by fusion score (FS) ranging from 1 (no alignment) to 5 (exact alignment). Angiography provided PA pressure (PAP), pulmonary vascular resistance (PVR), and PA wedge pressure (PAWP). Receiver operating characteristics (ROC) analysis was performed. Results: Twenty-nine patients were considered surgically amenable, and 20 patients were inoperable. Mean PAP, PVR, and PAWP were 48 ± 11 mmHg, 868 ± 461 dynes*sec*cm −5, and 11 ± 5 mmHg, without differences between surgical and non-surgical patients ( P > 0.5). In all patients accurate registration was reached (FS = 4.1 ± 0.7; range, 2–5). PVO and central OI separated PEA-amenable patients ( P ≤ 0.001) resulting in the area under the curve of 0.828 (cutoff for PVO: 37.8% with a sensitivity of 82% and specificity of 79%) and 0.755 (cutoff for central OI: 29% with a sensitivity and specificity of 86.2% and 79%) for operability. Conclusion: An accurate interpretation of rigidly registered CTPA and perfusion SPECT may contribute to stratification of operability in patients with CTEPH.